Multisystem inflammatory syndrome in children during the coronavirus disease 2019 (COVID-19) pandemic: a systematic review of published case studies - Yuyi Tang; Weiguo Li; Muna Baskota; Qi Zhou; Zhou Fu; Zhengxiu Luo; Yuan Shi; Yaolong Chen; Enmei Liu (2021)
Many cases have been reported recently on multisystem inflammatory syndrome in children (MIS-C), a newly emerged disease that seemed to correlate with coronavirus disease 2019 (COVID-19). The aim of this review was to describe the clinical features, treatment and outcomes of MIS-C, as well as to assess the risk of bias of published case studies, analyzing their reporting quality.We searched all articles reporting on multisystem inflammatory condition in children and adolescents in the context of COVID-19 through MEDLINE (via PubMed), Web of Science, China Biology Medicine disc (CBM) and China National Knowledge Infrastructure (CNKI) from their inception to June 17, 2020. We used CARE and IHE checklists to evaluate the risk of bias and quality of the included studies. We combined the data of clinical manifestations, imaging findings, treatments and outcomes using STATA version 15.Twenty-four studies were included, with a total of 270 participants. Most cases were from Europe and the United States, and the terms of MIS-C in different articles were varied. Fever and gastrointestinal symptoms were the most experienced symptoms. Shock, rash, conjunctivitis, lips or oral cavity changes, hand and feet anomalies, and lymphadenopathy were observed, while respiratory symptoms seemed relatively infrequent. Seventy-eight percent to 100% of patients had evidence of SARS-CoV-2 infection, and patients positive for SARS-CoV-2 by serology [86% (95% CI: 78%, 95%)] were more than those by RT-PCR [36% (95% CI: 26%, 46%)]. Most patients had one or more increased inflammatory markers including C-reactive protein (CRP), procalcitonin (PCT), erythrocyte sedimentation rate (ESR), ferritin, interleukin-6 (IL-6), and D-dimer, accompanied by neutrophilia and lymphopenia. Impaired cardiac function was seen from elevated biomarkers and abnormal echocardiography. Intravenous immunoglobulin (IVIG), anticoagulants, inotropic agents and glucocorticoids were the main treatments, along with other intensive supportive care. Overall, the outcomes of MIS-C were favorable, and only one death was recorded. In terms of the quality assessment of included studies, most of the case studies did not follow the standard reporting checklist, so that they failed to get higher scores in the risk of bias assessment.Patients with MIS-C present with symptoms more severe than children with COVID-19, with fever and gastrointestinal symptoms as the primary manifestations and multisystem involvement, particularly cardiovascular system. Longer follow-up and further researches for the pathophysiology of MIS-C are urgently needed. In addition, attention should be paid to the quality of case studies to improve the completeness and transparency of scientific reports.